A rehabilitation approach for rocking foundations: Vertical-monotonic and horizontal-cyclic loading. (15th October 2021) - Hadi Moosavian, S.M.; Ghalandarzadeh, Abbas; Hoseini, Abdollah
Highlights: A rehabilitation method has been presented with which to decrease the adverse effects of shallow foundation (SF) at low FSv values on system performance. The vertical bearing capacity of rehabiliated foundation (RF) using unattached piles (UP) was higher than the linear sum of UP capacity and SF capacity. The placement of UPs under the SF reduced settlement, residual rotation, and ξ while lateral capacity is slightly increased. As PD (pile distance from foundation edge) increased and UP became farther away from the foundation edge, the moment capacity decreased such that, despite the higher Lpile, the capacity decreased. Although the higher PD decreased the capacity and slightly increased settlement, a higher earthquake damping ratio was achieved with little further residual displacement. The SF moment capcity equation was modeified to calculate RF capacity considering the dependency of moment capacity to Lpile and PD. Abstract: Non-linear soil-structure interaction, in which the nonlinearity of the soil is investigated, could decrease the force demand in a superstructure and significantly dissipate earthquake energy. This is especially true for the rocking of shallow foundations, which could cause uplifting or sinking of a foundation depending on the vertical factor of safety (FSv ). Both could produce undesirable effects on system performance. For a shallow rocking foundation with a relatively low FSv, soil nonlinearity can cause significant foundation settlement. A rehabilitation approach is proposed in this research to decrease the undesirable effects on system performance for a rehabilitated foundation (RF) with a low FSv . In this approach, two unattached piles (UPs) have been placed underneath the shallow foundation edges to reduce foundation settlement and cause the transient regime to change from sinking to uplifting. A set of reduced-scale slow cyclic tests was performed on an SDOF structure with an RF to study the effect of pile length (Lpile ) and pile distance from the edge (PD) in 1 g test condition. Firoozkuh sand with 10% silt and a 5% moisture content was used. Before the main tests, the vertical bearing capacity was calculated using the results of vertical monotonic loading tests on both UPs and RF. The result of vertical loading tests shows that the vertical bearing capacity of the RF using UPs was higher than the linear sum of UP and shallow foundation capacity. Horizontal cyclic loading tests showed that placing UPs and increasing Lpile increased the system moment capacity and decreased settlement of the foundation, residual rotation, and the damping ratio. The results showed that, as PD increased as the UPs were placed farther away from the foundation edges, the moment capacity decreased, while the damping ratio increased with little extra residual rotation and settlement. Comparison of the results of horizontal loading tests suggested the need for modification of the moment capacity equation for the RF rehabilitated using UP. In the modified equation, the dependence of the moment capacity on Lpile and PD was considered.